2017
DOI: 10.3168/jds.2017-12719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partitioning the nonfiber carbohydrate fraction and neutral detergent fiber method on digestibility of carbohydrates by dairy cows

Abstract: Many nutrition models rely on summative equations to estimate feed and diet energy concentrations. These models partition feed into nutrient fractions and multiply the fractions by their estimated true digestibility, and the digestible mass provided by each fraction is then summed and converted to an energy value. Nonfiber carbohydrate (NFC) is used in many models. Although it behaves as a nutritionally uniform fraction, it is a heterogeneous mixture of components. To reduce the heterogeneity, we partitioned N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Over time, some weaknesses in the original equation were noted ( White et al, 2017 ), and methods to account for additional sources of variation were suggested ( Tebbe et al, 2017 ). Improvements to the discount equation used in NRC (2001) , which used diet TDN as a proxy for starch, have also been suggested ( de Souza et al, 2018 ).…”
Section: Summative Equation and Potential Improvementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over time, some weaknesses in the original equation were noted ( White et al, 2017 ), and methods to account for additional sources of variation were suggested ( Tebbe et al, 2017 ). Improvements to the discount equation used in NRC (2001) , which used diet TDN as a proxy for starch, have also been suggested ( de Souza et al, 2018 ).…”
Section: Summative Equation and Potential Improvementsmentioning
confidence: 99%
“…Therefore, Tebbe et al (2017) partitioned NFC into starch and residual organic matter (ROM; ROM = NFC − starch, where concentrations are as percentages of dry matter) so that additional sources of variation could be included in the equation. Based on the Lucas test ( Tebbe et al, 2017 ), NFC, starch, and ROM behaved as nutritionally uniform fractions ( Figure 4 ); however, the overall fits were better and standard errors of the intercept coefficients (i.e., estimated metabolic fecal content) were decreased for ROM and starch compared with NFC. Using average true digestibility coefficients for ROM and starch should result in greater accuracy in estimating DE than using the average true digestibility of NFC.…”
Section: Summative Equation and Potential Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrates and dried, ground samples of silages, feces, and refusals were assayed for DM (100°C for 24 h), ash (muffle oven at 600°C 2000). The NDI-ash and NDICP values were then used to calculate NDF as ash-free, CP-free, or both (Tebbe et al, 2017). Nonacidified urine, water, milk, and dried ground feed, refusal, and fecal samples were analyzed for minerals (OARDC STAR Laboratory, Wooster, OH) by inductively coupled plasma emission spectroscopy (Isaac and Johnson, 1985) after microwave digestion in nitric acid (Jones et al, 1991).…”
Section: Digestion Collection Samplesmentioning
confidence: 99%